Serum neurogranin measurement as a biomarker of acute traumatic brain injury - Yang, Jun (Clin Biochem, 2015)
OBJECTIVES: Neurogranin (NRGN) is a small neuronal protein that plays an important role in synaptic signaling by regulating calmodulin (CaM) availability. In this study, we developed an ELISA to measure NRGN quantitatively in serum samples from a cohort of acute traumatic brain injury (TBI) patients and a non-TBI control cohort, and explored the potential value of NRGN as a circulating biomarker for TBI. DESIGN AND METHODS: Recombinant His-NRGN protein was used to develop mouse monoclonal capture and rabbit polyclonal detection antibodies, and they were used to develop a sandwich ELISA. After validation, we used this ELISA to measure serum samples from a cohort of typical adult acute TBI patients (N = 76 TBI cases) and non-TBI control patients (N = 150 controls). RESULTS: The NRGN ELISA lower limit of detection was 0.055 ng/mL, lower limit of quantification was 0.2 ng/mL, and interassay CVs were ≤ 10.7%. The average recovery was 99.9% (range from 97.2–102%). Serum NRGN concentrations in TBI cases were significantly higher than in controls (median values were 0.18 ng/mL vs. 0.02 ng/mL, p < 0.0001), but did not discriminate TBI cases with intracranial hemorrhage (p = 0.09). CONCLUSIONS: We have developed a highly sensitive and reproducible ELISA for measuring circulating NRGN in blood samples. Serum NRGN concentrations in acute TBI patients were significantly higher than in controls, indicating that NRGN could have utility as a circulating biomarker for acute TBI. This report provides evidence to support larger and controlled TBI clinical studies for NRGN validation and prediction of outcomes.